Prevalence and prognostic implications of electrocardiographic left ventricular hypertrophy in heart failure: evidence from the CHARM programme. Issue 1 (4th September 2006) - Hawkins, N M; Wang, D; McMurray, J J V; Pfeffer, M A; Swedberg, K; Granger, C B; Yusuf, S; Pocock, S J; Östergren, J; Michelson, E L; Dunn, F G
Abstract : Background: Electrocardiographic left ventricular hypertrophy (ECG LVH) is a powerful independent predictor of cardiovascular morbidity and mortality in hypertension. Objective: To determine the contemporary prevalence and prognostic implications of ECG LVH in a broad spectrum of patients with heart failure with and without reduced left ventricular ejection fraction (LVEF). Methods and outcome: The Candesartan in Heart failure: Assessment of Reduction in Mortality and morbidity (CHARM) programme randomised 7599 patients with symptomatic heart failure to receive candesartan or placebo. The primary outcome comprised cardiovascular death or hospital admission for worsening heart failure. The relative risk (RR) conveyed by ECG LVH compared with a normal ECG was examined in a Cox model, adjusting for as many as 31 covariates of prognostic importance. Results: The prevalence of ECG LVH was similar in all three CHARM trials (Alternative, 15.4%; Added, 17.1%; Preserved, 14.7%; Overall, 15.7%) despite a more frequent history of hypertension in CHARM-Preserved. ECG LVH was an independent predictor of worse prognosis in CHARM-Overall. RR for the primary outcome was 1.27 (95% confidence interval (CI) 1.04 to 1.55, p = 0.018). The risk of secondary end points was also increased: cardiovascular death, 1.50 (95% CI 1.13 to 1.99, p = 0.005); hospitalisation due to heart failure, 1.19 (95% CI 0.94 to 1.50, p = 0.148); and composite major cardiovascular events, 1.35 (95% CI 1.12 to 1.62, p = 0.002). Conclusion: ECG LVH is similarly prevalent in patients with symptomatic heart failure regardless of LVEF. The simple clinical finding of ECG LVH was an independent predictor of a worse clinical outcome in a broad spectrum of patients with heart failure receiving extensive contemporary treatment. Candesartan had similar benefits in patients with and without ECG LVH.